ANALISIS KOMODITI BASIS KELAPA SAWIT PADA SETIAP KECAMATAN DI KABUPATEN MOROWALI - Nyoman Antriyani; Alimudin Laapo; Arifuddin Lamusa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This research aimed to analyze the sector of palm oil commodity base in everysub district in Morowali district. The research location was purposively determined witha consideration that Morowali district is one of the central areas and is potential in the field of oil palm plantations. The analytical method used waslocation quotient analysis (LQ). The results of theresearch shows that during 2012-2015, two sub districts had LQ values >1 which were Tanah Raya with the LQ value equal to 1.10, and Witaponda with thehighest LQ value equal 1.13.  These indicate that the two sub districts should be recognized as basis because they are able to meet the needs for their own region as well as for exports.  The LQ value of oil palm commodity in Morowalidistrict was 3.35 in average during 2012-2015.